2018
DOI: 10.1002/jmri.25967
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of hepatic iron in patients suspected of coexisting iron overload and steatosis using multi‐echo single‐voxel magnetic resonance spectroscopy: Comparison with fat‐saturated multi‐echo gradient echo sequence

Abstract: 3 Technical Efficacy Stage 2 J. Magn. Reson. Imaging 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
(97 reference statements)
1
21
0
1
Order By: Relevance
“…Additionally, the overall fat fractions of the patients in this study were relatively low. It should be noted that a recent study by Lin et al also did not find a strong effect of fat fraction on the resulting R2‐derived LIC in patients with a similar fat fraction range. It is not presently known whether similar results would hold in patients with higher fat fractions.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Additionally, the overall fat fractions of the patients in this study were relatively low. It should be noted that a recent study by Lin et al also did not find a strong effect of fat fraction on the resulting R2‐derived LIC in patients with a similar fat fraction range. It is not presently known whether similar results would hold in patients with higher fat fractions.…”
Section: Discussionmentioning
confidence: 75%
“…This study indicated that there was no significant difference in the calibration curves generated by the monoexponential and monoexponential + fat fraction signal decay models. Part of the reason is likely that any difference in R2* values produced by the different models is less significant that 21 also did not find a strong effect of fat fraction on the resulting R2-derived LIC in patients with a similar fat fraction range. It is not presently known whether similar results would hold in patients with higher fat fractions.…”
Section: Discussionmentioning
confidence: 80%
“… T2/T2* : Since R2 = 1/T2 and R2* = 1/T2*, we will talk about them indiscriminately. Iron content can be measured using spin-density projection-assisted R2 [ 51 , 52 ] or T2* transverse relaxation, for example with GRE sequences [ 16 , 28 , 40 , 53 ]. These methods are standardised across scanners [ 42 , 51 ] and commercially available (Resonance Health, Australia and Perspectum, UK, respectively).…”
Section: Mpmri Methods In Clinical Practicementioning
confidence: 99%
“…9.2–11.5% across field strengths (Siemens) [ 189 ]. Variability in mechanical waves used (40 Hz, 50 Hz, 60 Hz) [ 82 ] Diagnosis of iron overload High sensitivity (0.85–0.94) and specificity (0.92–1.00) for wide range of liver iron concentrations [ 52 , 190 ] T2* AUROC for stainable iron: 0.79–0.94 [ 16 , 28 ] No, a confounder that can be overcome by T2* or SE-EPI sequences [ 35 , 89 , 90 ] Diagnosis of NASH and disease activity Not applicable cT1 AUROC for NASH: 0.69–0.72 [ 85 , 102 ] cT1 AUROC for NAFLD: 0.93 [ 102 ] cT1 AUROC for ballooning: 0.84 [adapted from [ 32 ]] cT1 AUROC for NAS ≥ 5: 0.74 [ 102 ] AUROC for NASH: 0.58 [ 85 ] Diagnosis of steatosis Volumetric fat fraction of liver tissue (% fat) rather than PDFF available as HepaFatScan PDFF AUROC for steatosis grades: ≥ G1: 0.93 [ 85 ] ≥ G2: 0.96 [ 85 ] ≥ G3: 0.94 [ 85 ] Not applicable but can add PDFF [ 36 , 40 ] Diagnosis of fibrosis Not applicable but can combine with T1 or DWI or MRE [ 35 , 41 , 45 , 89 ] cT1 AUROC for fibrosis stages: ≥ F2: 0.63–0.79 [ 32 , 85 , 102 ] ≥ F3: 0.62–0.74 [ 32 , 85 , 102 ] F4: 0.72–0.85 [ 16 ] [adapted from [ 32 ]] …”
Section: Mpmri Methods In Clinical Practicementioning
confidence: 99%
“…Fat plays an interactive and aggressive role in the progression of diseases (fibrosis, cirrhosis and hepatocellular carcinomas) to the point that new studies and methodologies have been recently assessed to quantify liver fat and liver iron content by measurement of confoundercorrected proton density fat fraction and R2. 79 Thus, further data are needed to correctly determine the prevalence of NAFLD and metabolic syndrome among wider cohorts of NTDT and TDT patients, particularly in Western countries. The assessment of the presence of fat in the liver should be extensively performed during the radiologic evaluation of liver iron overload.…”
Section: The Role Of Iron Overloadmentioning
confidence: 99%